Dung beetles (Scarabaeidae: Scarabaeinae) attracted to carrion in Ghana, West Africa and evidence for adult food source plasticity - Philips, T. Keith; Sukhdeo, Christie A; Peck, Stewart B (African Entomology, 2023)
A study on dung beetles attracted to carrion using baited pitfalls was conducted in eight Upper Guinean wet and moist forest sites as well as one savannah site in Ghana, West Africa. A total of 42 species and 1380 individuals were collected from all sites. The highest diversity was found in the Shai Hills savannah with 19 species while the lowest total of only four species was collected in the Cape Three Points forest. The forest sites combined had seven unique species while the savannah locality had 12 unique taxa. Most carrion feeders belong to the genus Onthophagus; Onthophagus liberianus made up 23% of the total catch and together with the next nine most abundant species accounted for 78% of the specimens collected. Two dung beetle tribes of African savannah species not noted as carrion feeders were strongly attracted to vertebrate carrion and included a member of the Oniticellini, Latodrepanus caelatus (Gerst.) and the Onitini, Onitis cupreus Castelnau. Additionally, a forest species of Sisyphini, Neosisyphus angulicollis Felsche, that is uncommon on carrion was attracted to carrion in large numbers. For two species, Onthophagus liberianus and O. rufopygus, studied herein and previously in the Ivory Coast, the relative attractiveness of carrion and dung in each country varied greatly, demonstrating behavioral plasticity in food choice.